(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study was to compare businessmen and professionals in terms of their locus of control, emotional intelligence, and subjective well-being. The study explored the relationship of subjective well-being with locus of control and emotional intelligence among businessmen and professionals. Additionally, the study aimed to investigate the association between locus of control and emotional intelligence. The sample consisted of 302 businessmen and professionals from different districts of Bihar, India. The participants were selected using a purposive-cum-incidental sampling method. The researchers measured the participants’ subjective well-being using the Satisfaction with Life Scale (SWLS) developed by Diener et al. (1985) and Ed Diener et al.’s (2009) Scale of Positive and Negative Experience (SPANE). Furthermore, the locus of control scale developed by Julian Rotter (1966) was used to measure the participants’ locus of control. Finally, the participants’ emotional intelligence was assessed using a scale developed by Dr. Arun Kumar Singh and Dr. Shruti Narain. The study found a strong relationship between subjective well-being and locus of control. It also found that businessmen reported a higher level of subjective well-being than professionals, while professionals showed higher levels of locus of control and emotional intelligence than businessmen. Additionally, the study found a significant correlation between emotional intelligence and subjective well-being, locus of control and subjective well-being, and emotional intelligence and locus of control.